2015
DOI: 10.1016/j.neuroscience.2015.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Motor neurons with differential vulnerability to degeneration show distinct protein signatures in health and ALS

Abstract: The lethal disease amyotrophic lateral sclerosis (ALS) is characterized by the loss of somatic motor neurons. However, not all motor neurons are equally vulnerable to disease; certain groups are spared, including those in the oculomotor nucleus controlling eye movement. The reasons for this differential vulnerability remain unknown. Here we have identified a protein signature for resistant oculomotor motor neurons and vulnerable hypoglossal and spinal motor neurons in mouse and man and in health and ALS with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
83
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(91 citation statements)
references
References 42 publications
8
83
0
Order By: Relevance
“…Taken together with our current findings, these suggest that the discovery of inherent protective modifiers could be fundamental to the development of future successful combinatorial therapies [33, 6063]. It is of particular interest to note that mitochondrial pathways have been previously highlighted as a potential disease modifier in ALS [64].…”
Section: Discussionsupporting
confidence: 57%
“…Taken together with our current findings, these suggest that the discovery of inherent protective modifiers could be fundamental to the development of future successful combinatorial therapies [33, 6063]. It is of particular interest to note that mitochondrial pathways have been previously highlighted as a potential disease modifier in ALS [64].…”
Section: Discussionsupporting
confidence: 57%
“…FF motor neurons also fire at higher rates than S motor neurons [6], consistent with the greater requirement for proteins necessary for synaptic function, supplied from the cell body via efficient axonal transport [62]. A recent study also demonstrated that the molecular motor dynein, which mediates both ER-Golgi transport and retrograde axonal transport, is upregulated in more vulnerable motor neurons, such as hypoglossal and spinal motor neurons, compared to oculomotor neurons, which are less vulnerable in ALS [10]. Hence these studies, together with our findings, link inhibition of ER-Golgi transport, ER stress and axonal transport, to specific vulnerability of motor neuron subtypes to neurodegeneration in ALS.…”
Section: Discussionmentioning
confidence: 63%
“…However, strong evidence suggests the MN pools involved in eye movement and pelvic sphincter control are largely spared in ALS12. Moreover, within a given MN pool, differences in vulnerability between MN subtypes (e.g.…”
mentioning
confidence: 99%